BALANTIDIUM COLI infection, immune status and comorbidities: literature review - Silva de Oliveira (§), Amanda; Gómez-Hernández (§), César; Rezende-Oliveira, Karine (Revista de Patologia Tropical / Journal of Tropical Pathology, 2022)
ABSTRACT Balantidiasis, a disease caused by the ciliated protozoan Balantidium coli, mainly infects the large intestine and may present intestinal spread. The purpose of this literature review was to study the infection by B. coli and comorbidities to identify the factors that can contribute to the establishment of the disease. In this review, we attempt to explore and describe the various comorbidities associated with B. coli infection. We reviewed the literature based on comorbidities with a focus on the association with B. coli infection. The primary platforms targeted were PubMed, LILACS, SciELO and Google Scholar. Studies published between 1990 and 2020 in Portuguese, English, and Spanish were considered. The comorbidities reported in the papers were diverse, associating infection by B. coli with the immunosuppression that they generate. The intestinal microbiota may also play an important role, because when dysbiosis is present, its composition and structure are affected, which may enable the invasion of the mucosa. The review shows that the presence of the parasite and establishment of balantidiasis can influence in the clinical stage of chronic and autoimmune diseases, considering the modulation of the immune response in presence of B. coli. KEY WORDS: Balantidium coli; autoimmunity; balantidiosis; comorbidities; immunodepression.